Examining Malaysian leader characteristics in a manager-subordinate relationship - Haslina Halim,; Farah Lina Azizan, (Penerbit Universiti Kebangsaan Malaysia, 2017)
The paper discusses the findings of the first stage of data collection from a study on the characteristics of leaders in manager-subordinate relationship in Malaysian organizations. The findings are based on in-depth interviews conducted with focus groups involving Malaysian employees, which focused on employee perspectives on key qualities that leaders possess to uphold and maintain superior-subordinate relationship. The adoption of qualitative approach in this phase of data collection process is crucial in deriving leadership behaviors that are essential in the workplace. The identification of these behaviors could help us generate items for the final phase of our data collection process. The research takes into consideration the argument posed by Bass (2008), which has contended that methodological and substantive issues are likely to broaden through the combination of multiple research approaches such as qualitative interview and focus group discussion. The inclusion of eastern perspectives in a western model would bring a holistic description of a communication model. The interviews were conducted with the hope of identifying the themes of leader-characteristics which would help strengthen the relationships between a manager and his or her employees. This would facilitate further understanding of leader characteristics in superior-subordinate relationship. Eight themes emerged from the interviews. Consequently, this paper furthers theoretical contributions to the research on LMX, and expands the literature on superior-subordinate relationship in the workplace. The paper also highlights the limitations of the study for future research.